Religious Dialogue and Astronomy from the Perspective of Indonesian Muslim Scholars - Royyani, Muh Arif; Kibtyah, Maryatul; Adeni, Adeni; Rofiuddin, Ahmad Adib; Machzumy, Machzumy; Kholis, Nor (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Dialogue between religion and science is a necessity, because both of them can mutually reinforce the sources of Islamic law. The astronomical approach in the study of hadith makes a significant contribution to the development of astronomy. This article aims to examine the thoughts of an Indonesian Muslim scholar, namely Syamsul Anwar, who offers the concept of the interconnection of astronomy with hadith (especially astronomical hadith). This type of research is a literature by conducting a descriptive analysis of Syamsul Anwar's thoughts. The results of the study show that his contribution to the study of astronomy through an astronomical approach is able to strengthen understanding of the position of a hadith not only from a shari'ah perspective but at the same time being able to explain the meaning of a text using scientific principles (science). The study shows the importance of contextualization and interconnection between Islamic scholarship and other scientific fields. Thus, the efforts that have been made by Syamsul Anwar further strengthen the importance of dialogue between religion and science